THE EFFECT OF FINANCIAL LITERACY, INCOME, AND SELF-CONTROL ON FINANCIAL MANAGEMENT BEHAVIOUR IN STUDENTS - Ade Fitriani Kusuma Septiarum; Susanti Susanti (Jurnal Scientia, 2023)
Financial management is a skill that students should have in their lives. As a result, students should have an income, attend university finance classes, balance income and spending, comprehend the many sorts of financial activities, practice self-control over financial expenditures, and manage personal money. This study aims to examine the impact of financial literacy income, and self-control on student financial management behaviour. This is an associative quantitative study. Measurement of variables through a Likert scale. The population studied was the 2018 and 2019 Accounting Education Study Program students, totalling 117 students. The number of samples was determined using the Slovin formula for 91 students. The sampling approach employing the Non-Probability Sampling technique in conjunction with the Purposive Sampling technique. Techniques for collecting data using online surveys. This study report concludes that financial literacy, income, and self-control all substantially affect students' money management behaviour.